HOW PARENTS EDUCATION IMPROVE STUDENT ACHIEVEMENT? - Kurniaman, Otang; Indarni, Annisa; Noviana, Eddy (PrimaryEdu : Journal of Primary Education, 2021)
The Education in elementary school is a very important factor. Because the elementary school level is the foundation for the development of children's thinking and learning abilities influences and influences to the next level. The purpose of this research is to determine the academic achievement of students who are influenced by the parent’s education level. This research used a quantitative approach with a correlation test. The research conducted at Elementary school of 105 Tampan Pekanbaru to all of grade V students, with 150 total students. The Researcher used the Krejcie and Morgan tables sampling with 108 students. Based on the results of the correlation test shows that the magnitude of the father's education correlation coefficient on student academic achievement is 0.012 while the correlation of maternal education to student academic achievement is 0.081. Both are below the value of the r product moment correlation coefficient table for a sample of 108 with a significance level of 5% that is equal to 0.187. Thus the hypothesis H0 is accepted, it means that there is no meaningful relationship between parental education and student achievement.